2006
DOI: 10.1111/j.1365-2966.2005.09946.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of large-scale intrinsic ellipticity--density correlation from the Sloan Digital Sky Survey and implications for weak lensing surveys

Abstract: The power spectrum of weak lensing shear caused by large‐scale structure is an emerging tool for precision cosmology, in particular for measuring the effects of dark energy on the growth of structure at low redshift. One potential source of systematic error is intrinsic alignments of ellipticities of neighbouring galaxies [the intrinsic ellipticity—intrinsic ellipticity (II) correlation] that could mimic the correlations due to lensing. A related possibility pointed out by Hirata & Seljak is correlation betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
429
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(463 citation statements)
references
References 114 publications
32
429
1
1
Order By: Relevance
“…This was a clear signal of contamination of non-cosmological origin, probably PSF correction residuals. Also, intrinsic alignments of galaxies were detected at high significance even in the linear regime, at a level that represented a potentially serious systematic error even for then-ongoing surveys (Mandelbaum et al, 2006).…”
Section: Cosmic Shearmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a clear signal of contamination of non-cosmological origin, probably PSF correction residuals. Also, intrinsic alignments of galaxies were detected at high significance even in the linear regime, at a level that represented a potentially serious systematic error even for then-ongoing surveys (Mandelbaum et al, 2006).…”
Section: Cosmic Shearmentioning
confidence: 99%
“…Note that they predict only E-mode intrinsic alignments, because the alignments are linearly sourced by a scalar field. 58 Observations of LRGs in the SDSS have shown that the galaxy-ellipticity correlation 59 w ge (r p ) has the same power-law slope as the galaxy correlation function w g (r p ) ∝ r −0.7 (Mandelbaum et al, 2006;Hirata et al, 2007), with an amplitude that increases rapidly with LRG luminosity. This is a quantitative success of the linear model.…”
Section: Intrinsic Alignments*mentioning
confidence: 99%
See 1 more Smart Citation
“…While lensing by the intervening matter creates a tangential alignment of background source galaxies around the lens (Kaiser 1992), tides have the opposite effect, typically leading to a radial alignment of sources towards overdensities. Alignments across large separations were first measured by Brown et al (2002), with a subsequent confirmation by Mandelbaum et al (2006). This signal was shown to arise from the alignment of luminous red galaxies (Hirata et al 2007;Joachimi et al 2011;Singh, Mandelbaum & More 2014), while it has not been detected for late-type galaxies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we follow the notation of Mandelbaum et al (2006) to give formulae for the calculation of galaxy-intrinsic shear correlation function (ξg+(rp, Π)) and the projected statistic, wg+. Here, rp is the comoving transverse separation of a pair of galaxies in the XY plane and Π is their separation along the Z direction.…”
Section: Projected Shape Correlation Functionsmentioning
confidence: 99%